Trachemys scripta Eggs as Part of a Potential In Vivo Model for Studying Sea Turtle Egg Fusariosis - María Martínez-Ríos; Laura Martín-Torrijos; Javier Diéguez-Uribeondo (Journal of Fungi)
The fungal pathogens Fusarium keratoplasticum and Fusarium falciforme are responsible for the emerging infectious disease named sea turtle egg fusariosis (STEF). This disease affects all sea turtle species throughout the world, causing low hatching success and mass mortalities. In this study, we investigated the potential use of widely available and easy-to-handle eggs of the invasive alien red-eared slider turtle, Trachemys scripta, as part of an in vivo host model to improve our knowledge of the biological properties of the pathogens responsible of the STEF. Specifically, we performed in vivo experiments, in which T. scripta eggs were challenged with conidia of F. keratoplasticum isolated from diseased sea turtle eggs. We found that the pathogen could colonize and develop similar signs to those observed in nature and fulfill Koch’s postulates. The pathogen showed high virulence properties (e.g., high disease incidence, severity, and low hatching success) and its ability to modify the pH in both the egg surface and culture media, confirming previously described fungal pathogen models. These results support the use of T. scripta as an experimental in vivo host model for studying the biological characteristics of STEF, thus providing valuable insights into the mechanisms underlying the emergence of this fungal disease.